2009
DOI: 10.5194/angeo-27-1035-2009
|View full text |Cite
|
Sign up to set email alerts
|

Statistical visualization of the Earth's magnetotail based on Geotail data and the implied substorm model

Abstract: Abstract. We investigated the temporal and spatial development of the near-Earth magnetotail during substorms based on multi-dimensional superposed-epoch analysis of Geotail data. The start time of the auroral break-up (t=0) of each substorm was determined from auroral data obtained by the Polar and IMAGE spacecraft. The key parameters derived from the plasma, magnetic-field, and electric-field data from Geotail were sorted by their meridional X(GSM)-Z(proxy) coordinates.The results show that the Poynting flux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
62
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 49 publications
15
62
0
Order By: Relevance
“…7d) with the simple model for DR formation and evolution discussed in Section 1. In this simple model the DR forms near Earth (within ≥ − * X R 25 GSM E ), where for high solar wind energy input the DR forms within ≥ − * X R 20 GSM E and for low solar wind energy input the DR forms tailward of this region ( ≤ − * X R 20 GSM E ) (Nagai et al, 2005;Machida et al, 2009). After formation, the DR is expelled tailward towards larger negative * X GSM (Oka et al, 2011).…”
Section: Quasi-2d Calculation Of the Occurrence Ratementioning
confidence: 94%
See 1 more Smart Citation
“…7d) with the simple model for DR formation and evolution discussed in Section 1. In this simple model the DR forms near Earth (within ≥ − * X R 25 GSM E ), where for high solar wind energy input the DR forms within ≥ − * X R 20 GSM E and for low solar wind energy input the DR forms tailward of this region ( ≤ − * X R 20 GSM E ) (Nagai et al, 2005;Machida et al, 2009). After formation, the DR is expelled tailward towards larger negative * X GSM (Oka et al, 2011).…”
Section: Quasi-2d Calculation Of the Occurrence Ratementioning
confidence: 94%
“…Observations of the reconnection site have been made over a wide range of locations along the 2D magnetotail neutral sheet, where observations are typically discussed in terms of their dependence on * X GSM and * Y GSM . Machida et al (2009) analyzed several years worth of Geotail-observed substorm-related changes to the structure of the magnetotail magnetic field and plasma. They found that the average region where the reconnection site formed was ∼ R 20 E (Earth radii) down the magnetotail ( = − X R 20 = − * X R 15 GSM E (Miyashita et al, 2009;Eastwood et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the conclusion based on the analysis of Geotail observations [Asano et al, 2004;Miyashita et al, 2009], that the magnetic reconnection in the tail starts near the tailward edge of an intense cross-tail current, which extends from X ∼ −5 to −20 R E in the GSM coordinate system. Moreover, a distribution of the northsouth magnetic field B z similar to the specific profile shown in Figure 2a has recently been inferred from the statistical vizualization of the magnetotail Geotail data prior to the substorm onset (Machida et al [2009], see in particular, their Figure 2c). The formation of a thin current sheet embedded into a thicker plasma sheet and extended from near geosynchronous orbit to the mid -magnetotail (∼30 R E ) during the growth phase of a substorm has been shown using multisatellite measurements by Pulkkinen et al [1999].…”
Section: Multiscale Current Sheet Modelmentioning
confidence: 99%
“…Recent simulation studies that impose the convective electric field as a boundary condition at the magnetospheric lobe have shown that tearing instability and magnetic reconnection can be driven (Liu et al 2014;Pritchett 2005). Sitnov and Swisdak (2011) showed that the "X-point" (the point where oppositely directed magnetic-field lines reconnect) of magnetic reconnection forms on the tailward side of the B z -hump in the CS, as was found by Machida et al (2009;, because the electric energy of the Poynting flux is locally concentrated. The observational results reported in Machida et al (2009;, however, require simulations of both the DL field and the CS region.…”
Section: Introductionmentioning
confidence: 87%
“…A magnetic reconnection arises at X ∼ −20 Re as the consequence of the process. Machida et al (2009Machida et al ( , 2014 performed superposedepoch analyses with Geotail and THEMIS data to investigate the physical conditions in the magnetotail around the substorm onset. They have suggested a new substormtriggering model, namely, the "Catapult Current Sheet Relaxation" (CCSR) model, based on the results.…”
Section: Introductionmentioning
confidence: 99%